2020
DOI: 10.3390/app10165652
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Biochar and Clinoptilolite on Composition and Gaseous Emissions during the Storage of Separated Liquid Fraction of Pig Slurry

Abstract: The storage of animal manure is a major source of gaseous emissions. The aim of this study was to evaluate the effects of biochar and clinoptilolite on the composition and gaseous emissions during the storage of separated liquid fraction of pig slurry. The experiment was carried out using containers with 6 L of pig slurry each. The additives biochar and clinoptilolite were added alone and mixed to the pig slurry at a rate of 2.5% each, in a total of four treatments with three replicates including the control. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 38 publications
3
11
3
Order By: Relevance
“…where AD is the mean value of individual or cumulative gas values from slurries and their fractions with additives, and UN is the mean value of individual or cumulative gas values from untreated slurries. The cumulative emissions of NH 3 , N 2 O, CO 2 and CH 4 were determined by averaging the flux between two sampling occasions and multiplying by the time interval between the measurements [21,22]. Then, cumulative emissions were expressed as % of total N or C applied in each slurry and fraction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…where AD is the mean value of individual or cumulative gas values from slurries and their fractions with additives, and UN is the mean value of individual or cumulative gas values from untreated slurries. The cumulative emissions of NH 3 , N 2 O, CO 2 and CH 4 were determined by averaging the flux between two sampling occasions and multiplying by the time interval between the measurements [21,22]. Then, cumulative emissions were expressed as % of total N or C applied in each slurry and fraction.…”
Section: Discussionmentioning
confidence: 99%
“…The sedimentary origin of the clinoptilolite was Turkey (Zeolita Natural NUTRI-Clinoptilolita 1g568, ZeoCat Soluciones Ecológicas S.L.U., Barcelona, Spain), with the following characteristics: particle size < 0.425 mm; mineralogical composition of 915 g kg −1 for clinoptilolite, 35 g kg −1 for montmorillonite, 35 g kg −1 for feldspars, 15 g kg −1 for muscovite and 10 g kg −1 for cristobalite (by XRD analysis); chemical composition of 685 g kg −1 for SiO 2 , 110 g kg −1 for Al 2 O 3 , 29 g kg −1 for K 2 O, 31 g kg −1 for CaO, 11 g kg −1 for MgO, 4.5 g kg −1 for Na 2 O and 0.5 g kg −1 for TiO 2 ; cation exchange capacity (CEC) of 1.7 meq g −1 (by CEC method); apparent porosity of 47.5%; specific surface area of 75 m 2 g −1 (by Brunauer, Emmett and Teller method); pH (H 2 O) of 7.8; bulk density of powder of 750 kg m −3 ; moisture content of 65.7 g kg −1 . The rate of each additive was chosen considering previous studies [20,21], which recommended a maximum dosage of 5% (w/w) due to economic and practical issues.…”
Section: Slurries and Additivesmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-study demonstrated that the application of biochar causes a reduction in CH 4 , N 2 O and NH 3 emissions [ 77 ]. Recently, a study was focused on the analysis of commercial biochar stability in combination with clinoptilolite for the reduction in gas emissions [ 78 ].…”
Section: Application Of Engineered Biochar In Different Fieldsmentioning
confidence: 99%
“…The application of proper amendments such as biochar is a known efficacious and environmentally friendly method for reducing the availability and mobility of potentially toxic elements in contaminated soil via in situ immobilization [3,9]. Biochar is a sensible and robust material for the enhancement of soil fertility and management of contaminated soils for sustainable agriculture and mitigation of climate change [1,10]. Is a carbon-rich material that can be prepared from various organic waste feedstocks [1], like from various biomass, both woody (primarily residues from forestry and trees) and non-woody (agricultural crops and residues, animal waste, urban and industrial solid waste).…”
Section: Introductionmentioning
confidence: 99%